2016
DOI: 10.1097/mpg.0000000000001158
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Eosinophilic Gastrointestinal Disease in Children With Intestinal Failure

Abstract: Objectives To describe the prevalence and clinical features of gastrointestinal eosinophilic inflammation among pediatric patients with intestinal failure (IF). Methods Medical records of all patients followed in our institution's intestinal failure program who underwent GI endoscopy over a 15 year period were reviewed and clinical, pathologic, nutrition and laboratory data collected. Results One hundred and five patients underwent 208 GI endoscopic procedures with biopsy. The overall prevalence of eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…Histological features of EC show numerous eosinophil counts, > 50 cells/HPF in the right colon and 30 cells/HPF in the left/transverse colon [5]. Stamm et al reported a high prevalence of gastrointestinal eosinophilic inflammation in a large cohort of children with intestinal failure (IF) [6]. In this current case, eosinophilic inflammation was observed on blood and pathological examinations.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Histological features of EC show numerous eosinophil counts, > 50 cells/HPF in the right colon and 30 cells/HPF in the left/transverse colon [5]. Stamm et al reported a high prevalence of gastrointestinal eosinophilic inflammation in a large cohort of children with intestinal failure (IF) [6]. In this current case, eosinophilic inflammation was observed on blood and pathological examinations.…”
Section: Discussionmentioning
confidence: 50%
“…Prednisolone dose is often started at 0.5-2 mg/kg/day and tapered off after 1-2 weeks. Although most cases show temporary improvement, approximately 60% of patients experience recurrence of symptoms after treatment [6]. Prednisolone administration was effective in combination with other EGIDs treatment approaches.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown that short-bowel syndrome can lead to many chronic complications including esophagitis [12], diarrhea [13], hepatic steatosis and cholestasis [14], cholelithiasis, electrolyte and micronutrient deficiencies [15], metabolic bone disease [16], nephrolithiasis [17], d-lactic acidosis [18], and catheter-related complications [19].…”
Section: Discussionmentioning
confidence: 99%
“…There is a suggestion of increased risk of gastrointestinal allergic disease in infants with intestinal failure. One large single center review of infants with IF found that 40% had gastrointestinal eosinophilic inflammation, postulated due to abnormalities in intestinal permeability [ 20 ].…”
Section: Enteral Nutritionmentioning
confidence: 99%